1999
DOI: 10.1088/0029-5515/39/12/302
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 2: Plasma confinement and transport

Abstract: Physics knowledge in plasma confinement and transport relevant to design of a reactor-scale tokamak is reviewed and methodologies for projecting confinement properties to ITER are provided. Theoretical approaches to describing a turbulent plasma transport in a tokamak are outlined and phenomenology of major energy confinement regimes observed in tokamaks, including those with edge and internal transport barriers, is described. The chapter is focused on the energy confinement in the high confinement regime (H-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 955 publications
(180 citation statements)
references
References 355 publications
7
167
1
5
Order By: Relevance
“…The calculated ideal low-n stability limit to b N is found to be the largest in discharges with the broadest pressure profiles. Confinement of the thermal component of the plasma, when compared to the IPB98(y,2) scaling, 9 is as expected for H-mode. However, global confinement with q min > 2 is below what is typically associated with H-mode, as determined by a comparison to the ITER-89P scaling.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…The calculated ideal low-n stability limit to b N is found to be the largest in discharges with the broadest pressure profiles. Confinement of the thermal component of the plasma, when compared to the IPB98(y,2) scaling, 9 is as expected for H-mode. However, global confinement with q min > 2 is below what is typically associated with H-mode, as determined by a comparison to the ITER-89P scaling.…”
Section: Introductionsupporting
confidence: 60%
“…The figure shows the ratio of the thermal energy confinement time (s Eth ) to s 98 , the confinement time predicted by the IPB98(y,2) energy confinement scaling. 9 This value is referred to here as H 98 , the H-mode confinement scaling factor, although here the thermal energy confinement time is determined from the measured thermal pressure profile integrated over the plasma volume (W th ). The value of H 98 is usually determined for DIII-D by subtracting an estimate of the fast ion stored energy from the total stored energy obtained from an equilibrium reconstruction using the EFIT 27 code (W MHD ).…”
Section: Confinementmentioning
confidence: 99%
See 1 more Smart Citation
“…1,12 Shielding currents are excited by plasma rotation 1 or by a combination of pressure gradients and the characteristic favorable average magnetic field-line curvature present in tokamak plasmas. 13 The latter mechanism for exciting shielding currents is of particular significance for ITER, 14 because of the low intrinsic plasma rotation expected in this device. In addition to shielding currents at rational surfaces, an external magnetic perturbation excites currents that are distributed throughout the bulk of the plasma.…”
Section: -11mentioning
confidence: 99%
“…H-mode and hybrid plasmas were obtained with energy confinement enhancement factors (H 98 ) in the range of 0.9-1.2 [53] when compared with IPB98(y,2) scaling law [54]. It was previously reported that stationary H-modes could be re-established with the ILW by avoiding W accumulation through the production of frequent ELM regimes by gas puffing [12].…”
Section: Scenario Development and Optimizationmentioning
confidence: 99%